The Effect of Pretreatment by using Electron Beam Irradiation on Oil Palm Empty Fruit Bunch - A. Kristiani; N. Effendi; D. Styarini; F. Aulia; Y. Sudiyani (Atom Indonesia, 2016)
Oil palm empty fruit bunch (OPEFB) is a potential type of lignocellulosic biomass for second-generation bioethanol production. The pretreatment process is an important process in the series of processes to produce bioethanol. This research aims to study the effects of pretreatment process by using electron beam irradiation to OPEFB’s characterization as raw materials for the hydrolysis reaction to produce monomer sugars which will be fermented into ethanol. The untreated and treated OPEFB are characterized in terms of their physical and chemical properties. Analysis results of the compositional analysis by using NREL/TP-510-42618 method show that after pretreatment by using electron beam irradiation, OPEFB's total lignin content is changed little while its cellulose and hemicellulose contents tend to decrease with increasing irradiation dose. X-ray diffraction (XRD) analysis shows that there is a decrease of crystallinity compared to untreated OPEFB, except for 200-kGy irradiated OPEFB. The highest decrease of crystallinity was shown by 300-kGy irradiated OPEFB. Further, crystallite sizes of treated OPEFBs are not significantly different from the untreated, except for the 200-kGy irradiated OPEFB. Irradiation pretreatment also increases specific surface area, pore volume, and pore size. The IR spectra analysis show the absorption of cellulose, hemicellulose, and lignin.Received: 07 January 2015; Revised:15 May 2015; Accepted: 17 May 2015